Localization of myosin heavy chain A in the human pathogen Entamoeba histolytica. - Rahim, Z (1993)
To recognize myosin II in trophozoites of the human pathogen Entamoeba histolytica, a specific antimyosin polyclonal serum was raised against a fusion protein consisting of a 146-amino-acid fragment of the myosin II heavy chain A of E. histolytica (MhcA) fused with beta-galactosidase. The hybrid protein was encoded by a chimera gene formed by a DNA fragment, from the mhcA gene, amplified by polymerase chain reaction and fused with the lacZ gene of Escherichia coli. Polymerase chain reaction-amplified DNA is located within the region encoding the tail domain of myosin. This antibody recognized a 250-kDa protein in extracts of E. histolytica trophozoites. Confocal microscope analysis of antibody-labelled trophozoites indicated that MhcA localizes at the posterior pole of locomoting cells and concentrates within the uroid. These results might indicate that MhcA is involved in movement and in the uroid formation which help amoebas to escape the host immune response. These data are the first evidence indicating that myosin exists in E. histolytica. In addition, two other peptides were found in myosin-enriched extracts of amoebas, indicating that other myosins may be present in this parasite.